Fully reactive 3D inkjet printing of polydimethylsiloxane and polyurethane - Sturgess, Craig (2018)
Additive Manufacturing (AM) encompasses several different technologies, such as inkjet printing, extrusion, and laser melting processes, to selectively transform a processable phase, such as a liquid or powder, to a solid phase, e.g. through solidification, chemical reaction or powder melting and solidification. The geometry is initially defined as a 3D CAD model, which is subsequently ‘sliced’ to create a geometrical representation suitable for the layer-wise manufacturing process. These layers are “printed” in series on a substrate and are additively stacked. Some AM processes can also include multiple materials or voids in this process to increase the design freedom and geometric complexity. With any new process there are challenges, the key one for most AM processes is the limited material selection. Different processes have different material requirements and many current AM materials are sourced from other processes, for example a number of stereolithography processes use materials originally developed as finishes or coatings. The various AM processes have different criteria that must be met for a material to be suitable for processing, such as particle size and distribution, melting temperature and laser absorption in the case of laser-powder bed systems. This PhD is concerned with materials for ink jet printing, a major advantage of this process being the capability to co-deposit different materials. As the materials in jetting are not fed from a single bed or on a platform, there is complete control over material placement. The basic technology behind material jetting is the same as that seen in desktop inkjet printers, and the major challenge in transforming this to a 3D printing method is in materials development. Currently, the process is dominated by fast curing UV based resins, which are primarily acrylate based, and solvent based inks. The solvent inks highlight their 2D printing origins as they have a low material loading resulting in thin layers. These solvent systems are typically used to transport a conductive solute e.g. silver nanoparticles or graphene oxide. The focus of this PhD was to develop new materials for AM jetting by combining reactive components during processing. This process, called Fully Reactive Inkjet Printing (FRIJP), is only possible because of the freedom of material jetting to use multiple materials. In this work two reactions were selected for the development of FRIJP inks. The first was the crosslinking of polysiloxane based polymers (PDMS), the second was the addition polymerisation of polyurethane. These two reactions schemes were chosen because they involve the combination of two different reactive species and produce no unwanted by-products. For the FRIJP of PDMS a commercial two-part chemistry was used that separated the cross-linker and catalyst. When these two components are combined they produce a transparent PDMS rubber. The PDMS was found to have a viscosity that was too high for inkjet printing so a compatible solvent was selected and the concentration modified. Once a printable ink had been created, trials were conducted which involved printing the two components onto a substrate. It was found that by control of the mixing ratio and substrate heating, high reaction rates could be achieved and complex designs could be printed. These designs were then analysed using FTIR and Raman spectroscopy and it was found that there was comparable curing to the bulk mixing. It was also determined that for the selected PDMS there were no issues with substrate mixing which would result in concentration gradients. The second reaction investigated was the addition polymerisation of polyurethane, which involves combination of the diol and diisocyanate. For this work, the inks were developed from monomers that had printable viscosities through thermal modification. However, one ink used did contain a low concentration of solvent. For the polyurethane work the printing environment was controlled to minimise the moisture which could produce unwanted polyurea and amines. The metric used to determine how suitable the inks were for inkjet printing was the molecular weight of the polymer chain. The analysis was conducted using Size Exclusion Chromatography on the printed samples. It was found that after in development, it was possible to achieve an average molecular weight over 20,000, which was identified as the point whereby the polymer printing was successful. This PhD also demonstrates that when printing these two chemistries, the small size of the droplets facilitates complete mixing of the inks. Importantly, with the immiscibility of the polyurethane monomers before reaction, it was found that the small droplet size allowed for the reaction and successive molecular diffusion to achieve the high degrees of conversion required for the production of functional polymers.